On-Street Parking and Traffic Flow Performance at Kapasan Shopping Area Surabaya - Amrita Winaya (Universitas Islam Sultan Agung, 2020)
Traffic congestion is a problem that is often faced by Indonesian big cities. It is related to land use in an area that causes on-street parking. The main cause is the imbalance between demand and supply, namely the need for parking during rush hour exceeds the capacity of existing parking. Another consequence is the increasing of side barriers resulting in the delays on certain roads. Shopping area in Jl.Kapasan, Surabaya is one of the densely areas attracted most people of Surabaya to conduct trading activities and shopping for daily needs. The denstiy of this region will affect the performance of traffic flow and causing delays.The study aims to identify on-street parking in Jl.Kapasan shopping area, consequences arising from parking on the road, and determine the level of service or performance of roads around this shopping area. The analytical methods used are derived from Indonesian Highway Capacity Manual 1997. Based on calculation and analysis, the capacity of Jl.Kapasan without parking on the road was 1468 pcu/hour and with on-street parking was only 1276 pcu/hour.